CONTROL OF TYROSINE AMINOTRANSFERASE SYNTHESIS IN TISSUE CULTURE BY A FACTOR IN SERUM - Gelehrter, Thomas D. (1969)
The hormonal induction of tyrosine aminotransferase in an established line of rat hepatoma cells is enhanced by the presence of a macromolecular component of serum in the inducing medium. The addition of serum to cells previously induced in serum-free medium results in a rapid two- to threefold increase in the rate of tyrosine aminotransferase synthesis, as measured by specific radio-immunoprecipitation techniques, as well as a smaller increase in over-all protein synthesis. The stimulation of protein synthesis by serum is accompanied by an increase in the proportion of ribosomes sedimenting as polysomal aggregates. The increase in the rate of TAT synthesis is largely independent of RNA synthesis as it is insensitive to antinomycin D, suggesting that the serum acts at a site beyond gene transcription. The maximum effect of serum on TAT synthesis requires the continued presence of the hormone inducer.